Preliminary Study on EGCG-Enhanced Vanadium Toxicity in Cells: Impact on Oxidative Stress - Ewa Wnuk; Iwona Zwolak (Molecules)
Environmental pollution by heavy metals (HMs) has become a serious threat in recent years due to their potential consequences for human health and life. One such metal is vanadium (V). Despite its numerous benefits—including antibacterial, antifungal, and anticancer properties—V induces cellular damage through oxidative stress. Epigallocatechin gallate (EGCG), a potent antioxidant found in large quantities in green tea, is considered an effective protector against the damaging effects of HMs on cells. The aim of this study was to evaluate the possible effect of EGCG on CHO-K1 cells exposed to V. This is the first experiment of its kind on healthy cells. Cells were treated with V and EGCG for 24 h, either in combination or separately. The doses were selected in a preliminary stage of the experiment (V 50 and 100 µM; EGCG 0.5 and 1 µM). As part of the study, the cell viability, total ROS activity, and mitochondrial membrane potential were assessed. The results showed that at the tested concentrations, EGCG did not reduce the toxic effect of V on cells, but in fact exacerbated its adverse effects on cells. Further studies are needed to understand the exact mechanism of V–EGCG interaction in mammalian cells.